Group Psychotherapies in Eating Disorders - F. Elif Ergüney Okumuş; Ezgi Deveci (Psikiyatride Güncel Yaklaşımlar, 2019)
Eating disorders are one of the major psychiatric disorders that cause serious health problems. Although treatment methods are highly developed, the desired treatment level has not been reached yet. So, a full remission can only be achieved in half of the patients who applied for treatment. For a full recovery, a long-term treatment model which has been applied by a multidisciplinary team is recommended, but these treatments can be very costly. As in all psychological problems, it is very important to handle relational factors in the treatment of eating disorders and it is considered that if relational factors are the focus of interventions, it will enhance the effectiveness of treatment. This study examines how group psychotherapies are applied in different types of eating disorders, their theoretical origins, the focuses of practice and their effectiveness. In the light of the findings, it is understood that group psychotherapies are promising therapeutic options in terms of therapeutic efficacy and cost-effectiveness, which can be preferred for appropriate cases.